Educação Infantil, currículo, BNCC: campos de experiência - Coelho, Regina Célia Machado (2023)
The present work studies childhood in Brazil as a historical and social subject, based on Philippe Arièés, in his work: “História Social da Criança e da Família”, the work of the teacher in early childhood education (OLIVEIRA, 2019), the analysis of the main regulatory documents for Early Childhood Education, from the Federal Constitution of 1988, which begins a look at early childhood education, the Statute of the Child and Adolescent (ECA); the Law of Guidelines and Bases (LDB), the National Curricular Guidelines for Early Childhood Education (DCNEI), the National Education Plan (PNE) up to the 2017 National Common Curricular Base (BNCC), mandatory reference for the preparation of curricula and pedagogical proposals for early childhood education, elementary and high school in Brazil. The planning of the kindergarten teacher and the teacher of the first year of elementary school, the curriculum of the city of São Paulo and bibliographical research were also considered. This research will have as methodological procedures a predominant Qualitative-predominant qualitative approach (CHIZZOTTI, 2003; GIL, 2002, LÜDKE; ANDRÉ, 2020) and Descriptive-descriptive, resulting from a documentary research through the analysis of official documents of a school, in which the researcher will seek data to answer the question: “How are learning rights articulated in the transition from early childhood education to entering the first year of elementary school?” This study prioritized the narrative and the author's professional and personal experience, both in the public and private systems, as a driving force, enabling the understanding and carry out of the activities registered in this work